ENHANCING THE TEACHING OF THE ENGLISH LANGUAGE THROUGH ARTIFICIAL INTELLIGENCE IN A GLOBALISED WORLD - Ogechukwu Mary Nwanna (Universitas Ngeri Malang, 2025)
This study examined the teaching of English Language through Artificial intelligence in a globalised world focusing on how AI assisted language learning and teaching across the globe. These areas such as vocabulary, syntax and lexis have been greatly influenced by AI, hence making the learning and teaching of English Language accessible, understandable and simpler. Even though, the English Language has gained wider acceptance and used in virtually all the sectors, yet second language learners still have problems navigating in the areas of forming correct sentences, right spellings and correct usage of words. The study relied on systemic functional linguistic theory by M.A.K Halliday which stated that language is viewed as a source for making not only one meaning at a time but several strands of meaning simultaneously. It is equally excellent in understanding how English is used in context focusing on the function of language to create meaning in social situations. The study would also rely on technological mediation theory by Verbeek which asserted that AI is not just a neutral tool but as an agent that shapes linguistic practices and identities. A descriptive qualitative design was used to examine grammar conformity, lexical choices and syntactic structures. Data were collected using structured questionnaires. Findings from the study revealed that wrong syntactic structure, poor lexical choices and inadequate grammar conformity were the problems encountered in the teaching and learning of English Language. The study concluded that teaching and learning of English language through artificial intelligence is crucial because it makes the learning of English easier and simpler for language learners. The following recommendations among others were made which includes that teachers should master the use of proper lexical words, adequate grammar conformity and syntactic structure in to enhance English Language teaching and learning. The study contributed to existing knowledge by providing rich empirical data on the relationship between English Language and artificial intelligence for efficient language teaching and learning.